Dari Good Governance Ke Sound Governance: Reformasi Prinsip Dan Regulasi Pelayanan Publik Di Badan Penanaman Modal Dan Pelayanan Perizinan Terpadu Kabupaten Lima Puluh Kota - Nasrizal Nasrizal; Afriva Khaidir; Syamsir Syamsir (Jurnal Public Administration, Business and Rural Development Planning, 2019)
This research is start from the various problems in practical reformation and inovation of local goverment in public service realization, especially in implementation of investment affair and integrated license service. Based on data and result of analysis are found that realization of reformation and public service inovation in Board of Investment and Integrated License Service at Lima Puluh Kota Regency is not running well. Reformation practical and public sevice inovation all this time have many problems because of minimum budget factor, less of human resources, minimum of tools and infrastructures and information technology. Public service approach that are used is based on good governance principles with Structural Adjustment Programs (SAPs) pattern that have standardized in Standard Operational System (SOP) that tend to awkward and the dimensions of sound governance is not fulfill yet. Based on the riil condition from realization of reformation and inovation that public service, it can be arranged the ideas to reform the principle and public service regulation in Board of Investment and Integrated License Service at Lima Puluh Kota Regency.